IMPACT OF SUSPENSION OF CUSTOMS DUTIES AND QUANTITATIVE RESTRICTIONS ON IMPORTS FROM UKRAINE ON PURCHASE PRICES OF SELECTED AGRICULTURAL COMMODITIES IN POLAND IN 2022-2024 - Benedykt Pepliński; Karol Wajszczuk (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The EU’s liberalization of agricultural trade with Ukraine in mid-2022 triggered widespread farmer protests in all bordering countries. Farmers attributed the decline in commodity prices to excessive imports of agricultural products from Ukraine. The aim of this research was to determine the impact of wheat, corn, and barley imports on purchase prices in Poland. To this end, comparative analyses were conducted on purchase prices in five EU countries bordering Ukraine and three Central European countries. These prices were contrasted with average EU purchase prices and Polish purchase prices, categorized by proximity to the Ukrainian border. The analyses employed arithmetic means, weighted averages, and 12-month moving averages. The findings indicate no clear impact of Ukrainian imports on purchase prices in the analyzed countries. Even in neighboring countries experiencing significant imports from Ukraine, purchase price trends for individual cereals varied. This suggests that additional domestic factors influence cereal purchase prices in each country. Similarly, in Poland, no definitive correlation between imports and price levels could be established.